Collaboration For Social Justice: Islamic Philanthropy, Government, And Communities In Advancing Welfare In Marginalized Areas - Putra, Muhammad Deni; Fadilla, Siti; Shahmi, Mohammad Aliman; Mansur, Muhammad; sahroni, Abdulla; Hamzah, Muhammad Maulana (TAMWIL : Jurnal Ekonomi Islam, 2024)
Cross-sector collaboration between the government, philanthropy, and local communities is key to enhancing welfare in marginalized areas. This research employs qualitative methods through a literature review to analyze the role of this collaboration in creating policies and programs that are more responsive to community needs. The findings indicate that active involvement of local communities in welfare initiatives is crucial for the success and sustainability of these programs. This involvement fosters a sense of ownership and accountability, as well as strengthening transparency and feedback between the government and the community. However, cross-sector collaboration faces challenges such as the lack of structured platforms, communication issues, and differing priorities. To address these barriers, it is essential to establish formal mechanisms for collaboration, build effective communication channels, and engage all stakeholders in open dialogue. Community-based approaches also contribute to more relevant and effective solutions for social issues. These findings highlight the importance of fair and inclusive collaboration to create sustainable and responsive welfare systems in society.